Pengaruh Capital Expenditure, Net Working Capital dan Investment Opportunities terhadap Cash Holding - Ardhana, Delia; Honesty, Fiola Finomia; Honesty, Helga Nuri (Jurnal Eksplorasi Akuntansi, 2025)
The purpose of this study is to analyze the effect of capital expenditure, net working capital, investment opportunities on cash holding in manufacturing companies in the basic and chemical industry sectors listed on the Indonesia Stock Exchange (IDX) for the period 2020-2023. This research is quantitative research. The sampling technique used purposive sampling. The number of samples during the study year amounted to 73 data. The statistical method used is multiple linear regression analysis. The results showed that capital expenditure has a significant negative effect on cash holding, net working capital has a significant positive effect on cash holding and investment opportunities have no significant effect on cash holding in manufacturing companies in the basic and chemical industry sectors in 2020-2023.